PENINGKATAN KEMAMPUAN MENULIS TEKS BIOGRAFI MELALUI METODE PENGAJARAN LANGSUNG PADA SISWA KELAS X TITL SMK NEGERI 2 BANGKALAN TAHUN PELAJARAN 2019/2020 - Ribut Rahmat Jaya (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2021)
ABSTRACT. This study aims to improve text writing skills biographies using direct teaching methods to class X students X TITL SMKN 2 Bangkalan. This research is a classroom action research. The subjects in this study were all students of class X TITL SMK Negeri 2 Bangkalan in the academic year 2019/2020, totaling 32 students. The classroom action research was carried out in two cycles, each of which consisted of planning, acting, observing, and reflecting. In collecting research data, the authors used test techniques and non-test techniques. The test technique is the result of writing a biographical text using the direct teaching method. The non-test technique is the result of observing student activity. The data were analyzed qualitatively and quantitatively. From the observations there was an increase in the ability to write biographical texts in class X TITL SMK Negeri 2 Bangkalan. In the first cycle the class average reached 70.97 in the sufficient category. In the second cycle, the class average score was 76.4 in the good category. Classical completeness in cycle I reached 65.6% and in cycle II increased 18.8% to 84.4%.